A Framework on New Travel Demand Model Based on Potential Travelers and Surrounding Land Uses for Rapid Transit - Abal Abas, Z. (International Journal of Human and Technology Interaction (IJHaTI), 2017)
One of the public transports is rapid transit, which provides the highest performance mode of urban transportation. Currently, existing rapid transit travel demand analysis from the service provider is based on ticketing data that contain information such as time travel, origin and destination; which is using trip based method. This method has its limitation such as the demand is for trip making rather than for activities as well as having spatial, temporal and demographic aggregation errors. It also failed to predict the travel demand when there is future development or growth in the surrounding area. Therefore, new method for modeling travel demand is needed. This paper proposes a framework of new model and analytics for travel demands of rapid transits based on big data of potential travelers and surrounding land uses. Land uses and transportation are interdependent. With this proposed concept, the accurate travel demand for rapid transit in the future will be met. Therefore, the rapid transit service will have excellence operation, which includes optimum frequency, punctuality and reliable service.